Central nervous system involvement in adult acute lymphoblastic leukemia at diagnosis: results from the international ALL trial MRC UKALL XII/ECOG E2993. - Lazarus, H; Richards, S; Chopra, R; Litzow, MR; Burnett, A; Wiernik, P; Franklin, I; Tallman, MS; Cook, L; Buck, G; Durrant, I; Rowe, J; et al. (2006)
Outcome of acute lymphoblastic leukemia (ALL) in adults with central nervous system (CNS) disease at diagnosis is unclear. We treated 1508 de novo ALL patients with 2-phase induction and then high-dose methotrexate with l-asparaginase. Patients up to 50 years old in first remission (CR1) with a matched related donor (MRD) underwent an allogeneic stem cell transplantation (SCT); the remainder in CR1 were randomized to an autologous SCT or intensive consolidation followed by maintenance chemotherapy. Philadelphia chromosome (Ph)-positive patients were offered a matched unrelated donor (MUD) allogeneic SCT. Seventy-seven of 1508 (5%) patients a median age of 29 years had CNS leukemia at presentation; 13 of the 77 (17%) had Ph-positive ALL. Sixty-nine of 77 (90%) patients attained CR1. Thirty-six patients underwent transplantation in CR1 (25 MRD, 5 MUD, and 6 autografts). Eleven of 25 patients with MRD transplantation remain alive at 21 to 102 months, 2 of 5 with MUD at 42 and 71 months, and 1 of 6 with autologous SCT at 35 months. Seven of 27 treated with consolidation/maintenance remain in CR1 56 to 137 months after diagnosis. Overall survival at 5 years was 29% in those with CNS involvement at diagnosis versus 38% (P = .03) for those without. CNS leukemia in adult ALL is uncommon at diagnosis. Adult Ph-negative ALL patients, however, can attain long-term disease-free survival using SCT as well as conventional chemotherapy.